(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Indigenous People have a harmonious relationship with their surrounding environment. They possess knowledge of equitable and sustainable use of Nature and its resources. The polar opposite of this grateful relationship with Nature is the attitude that treats nature and its resources as instruments for fulfilling wants without caring about the loss incurred. This paper aims to illustrate the juxtaposition of two contrasting representations of nature- the indigenous perspective and the exploiters’ perspective in Linda Hogan’s People of the Whale. The indigenous perspective sees nature as their saviour. Nature is at the core of their identities. On the other hand, exploiters see nature as exotic and thus find it adventurous to explore. Such explorations are mostly greed-driven which compromises the natural balance. For this greed-driven exploration, these exploiters can go to any limits. They can subdue the original connections of the indigenous people with nature and misinterpret them as being the real agents of damage to nature. The exploiters come to know the best utilization of a particular natural produce through the tribals. Then they start capitalizing it thus causing a large-scale disruption and imbalance. The exploiters pose as saviours of nature. The conflict that ensues from such juxtaposition eventually leads to the damage of nature on a much larger scale.